Who Supports Populism and What Attracts People to It?. (June 2016) - Spruyt, Bram; Keppens, Gil; Van Droogenbroeck, Filip
In this paper, we engage with the emerging literature that studies the support for populism by means of attitudes among the public at large. More specifically, our paper has two objectives. First, we extend recent research by Akkerman et al. by showing that their measure performs rather well in a context that differs from the one it was originally formulated in. Data from Flanders (the Dutch speaking part of Belgium, N = 1, 577) also demonstrate that the support for populism can be empirically distinguished from feelings of lack of external political efficacy. Second, this is one of the first studies that assess who supports populism and why they do so. We show that populism is embedded in deep feelings of discontent, not only with politics but also with societal life in general. Moreover, we demonstrate that populism is strongest supported by stigmatized groups who face difficulties in finding a positive social identity. In the conclusion, we discuss the implications of our findings.